Praktik Manajemen Zakat Perspektif Hukum Islam; Analisis Komparatif Fikih Klasik dengan Fikih Kontemporer - Mayyadah Mayyadah (Universitas Islam Negeri Alauddin Makassar, 2019)
Practise of zakah management has developed and changed according to the times. Among the examples of these changes are the type of zakah that aren’t found in Prophet era, dynamic grouping of mustahik which varies from one society to society, and also amil problem in need to new terms and requirement.This paper aims to explore zakah management practise and it development from classic fikih compared to contemporary fikih perspective.